Evolutionary patterns of major urinary protein scent signals in house mice and relatives. Issue 15 (31st July 2019) - Sheehan, Michael J.; Campbell, Polly; Miller, Caitlin H.
Abstract: Scent marks are important mediators of territorial behaviour and sexual selection, especially among mammals. The evolution of compounds used in scent marks has the potential to inform our understanding of signal evolution in relation to social and sexual selection. A major challenge in studies of chemical communication is that the link between semiochemical compounds and genetic changes is often unclear. The major urinary proteins (MUPs) of house mice provide information on sex, status and individual identity. Importantly, MUPs are a direct protein product of genes, providing a clear link between genotype and phenotype. Here, we examine the evolution of urinary protein signals among house mice and relatives by examining the sequences and patterns of mRNA expression of Mup genes related to urinary scent marks. MUP patterns have evolved among mouse species both by gene duplication and variation in expression. Notably, protein scent signals that are male specific in well‐studied inbred laboratory strains vary in sex‐specificity among species. Our data reveal that individual identity signals in MUPs evolved prior to 0.35 million years ago and have rapidly diversified through recombining a modest number of amino acid variants. Amino acid variants are much more common on the exterior of the protein where they could interact with vomeronasal receptors, suggesting that chemosensory perception may have played a major role in shaping MUP diversity. These data highlight diverse processes and pressures shaping scent signals, and suggest new avenues for using wild mice to probe the evolution of signals and signal processing.